Sophorolipid Suppresses LPS-Induced Inflammation in RAW264.7 Cells through the NF-κB Signaling Pathway - Ruiqi Xu; Ling Ma; Timson Chen; Jing Wang (Molecules, 2022)
Objectives: Biosurfactants with anti-inflammatory activity may alleviate skin irritation caused by synthetic surfactants in cleaning products. Sophorolipid (SL) is a promising alternative to synthetic surfactants. However, there are few reports on the anti-inflammatory activity of SL and the underlying mechanism. The purpose of this work is to verify that lipopolysaccharide (LPS)-induced inflammation could be inhibited through targeting the pathway of nuclear factor-κB (NF-κB) in RAW264.7 cells. Methods: The influence of SL on cytokine release was investigated by LPS-induced RAW264.7 cells using ELISA. The quantification of the protein expression of corresponding molecular markers was realized by Western blot analysis. Flow cytometry was employed to determine the levels of Ca2+ and reactive oxygen species (ROS). The relative expression of inducible nitric oxide synthase (INOS) and cyclooxygenase-2 (COX-2) was determined by RT-PCR. An immunofluorescence assay and confocal microscope were used to observe the NF-κB/p65 translocation from the cytoplasm into the nucleus. The likely targets of SL were predicted by molecular docking analysis. Results: SL showed anti-inflammatory activity and reduced the release of inflammatory cytokines including interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and nitric oxide (NO). The experimental results show that SL suppressed the Ca2+ and ROS levels influx in the LPS-induced RAW264.7 cells and alleviated the LPS-induced expression of iNOS and COX-2, the LPS-induced translocation of NF-κB (p65) from the cytoplasm into the nucleus, and the expression of phosphorylated proteins such as p65 and IκBα. Furthermore, molecular docking analysis showed that SL may inhibit inflammatory signaling by competing with LPS to bind TLR4/MD-2 through hydrophobic interactions and by inhibiting IKKβ activation through the hydrogen bonding and hydrophobic interactions. Conclusion: This study demonstrated that SL exerted anti-inflammatory activity via the pathway of NF-κB in RAW264.7 cells.